Interleukin 33 mediates hepatocyte autophagy and innate immune response in the early phase of acetaminophen-induced acute liver injury. (30th May 2021) - Wang, Zengbin; Wu, Linqing; Pan, Banglun; Chen, Yizhong; Zhang, Tao; Tang, Nanhong
Highlights: Acetaminophen (APAP) induces elevation of IL-33 in vivo and vitro. IL-33 deficiency exacerbates acetaminophen-induced acute liver injury. Blockage of IL-33 regulates hepatic innate immune response post-treated with APAP. IL-33 modulates hepatocyte autophagy via AMPKα/mTOR signaling pathway. Abstract: Despite interleukin 33 (IL-33) functions as an "alarmin" released from hepatic dead cells in response to tissue damages, the interrelationship between IL-33-mediated hepatocyte autophagy and innate immune response in the acetaminophen (APAP)-induced liver injury (AILI) process remains obscure. This study aimed to explore the regulation of IL-33 on hepatocyte autophagy and macrophage polarization after APAP challenge in vivo and vitro . We found IL-33 released from hepatic necrosis was elevated in the AILI mouse model. Blockage of IL-33 exacerbated liver injury by consuming liver-resident macrophages cells (Kupffer cells, KCs) and promoting hepatic inflammatory factors secretion, such as TNF-α, IL-6 and IL-1β in the early phase of liver injury. Interestingly, IL-33 deficiency further activated hepatocyte autophagy and disrupted M2 macrophage polarization post-APAP challenge in vivo and vitro, which can be reversed by recombinant IL-33 treatment. Mechanistically, administration of IL-33 can directly enhance M2 polarization via PI3K/Akt signaling pathway and activate protective hepatocyte autophagy via AMPKα/mTOR signaling pathway in the AILI process. In conclusion, our data firstly demonstrates that IL-33 exerts protective effects on hepatocytes through the activation of autophagy and functions as an innate immunity regulator mediating macrophage polarization in the early phase of AILI.